Technological Development and Innovation in Knowledge Management - Castanha, Rafael Gutierres [UNESP]; Santos, Fernanda Bochi dos [UNESP]; Macucule, Augusto Junior (Univ Estadual Campinas - Sistema Bibliotecas, 2025)
Introduction: Intellectual production on Knowledge Management is evident in research across various fields such as Administration, Management, Information Science, Marketing, among others, focusing on sustaining organizations and companies within their market segments. Objective: To analyze technological development and innovation based on patent productions in knowledge management. Methodology: A patentometric study utilizing the search term knowledge management in the Derwent Index Innovation database for data collection related to patents on knowledge management, resulting in a total of 1311 results. Subsequently, the temporal evolution of patent applications, main patent areas, co-occurrence among international patent classifications, and cooperation among organizations or inventors were analyzed. Results: A growing trend of patent applications in Knowledge Management was observed between 1992 and 2024, with engineering and Computer Science being the areas of highest concentration, and the most representative international patent classification codes being: G06N, G06F, G06Q, and H04L. Regarding cooperation, major collaborations occurred among organizations such as IBMC, Hitachi Ltd., Hewlett-Packard Company, and Oracle. Conclusion: Patent applications in knowledge management are experiencing significant growth, with certain organizations standing out, particularly in the development of artifacts and/or industrial processes related to Engineering and Computing, represented by classifications G06F, G06Q, G06N, and H04L.
Keywords: Knowledge management; Innovation; Industrial property; Patentometrics